A solução do sistema {
x + y = 2
2x − y = 1
é:
A) x = 1 e y = 1
B) x = 2 e y = 1
C) x = 3 e y = 2
D) x = 1 e y = 2
Soluções para a tarefa
Respondido por
0
Explicação passo-a-passo:
Somando as equações:
x + 2x + y - y = 2 + 1
3x = 3
x = 3/3
x = 1
Substituindo na primeira equação:
x + y = 2
1 + y = 2
y = 2 - 1
y = 1
Logo, x = 1 e y = 1
Letra A
Perguntas interessantes
Matemática,
9 meses atrás
Português,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás